2023
DOI: 10.1101/2023.12.18.572097
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure and mechanism of Zorya anti-phage defense system

Haidai Hu,
Thomas C.D. Hughes,
Philipp F. Popp
et al.

Abstract: SummaryZorya is a recently identified and widely distributed bacterial immune system, which protects against phage invasion. It consists of a predicted membrane-embedded complex (ZorAB) and soluble components that differ among Zorya subtypes, notably ZorC and ZorD, in type I Zorya systems. Here, we reveal the molecular basis of the Zorya defense system using cryo-electron microscopy, mutagenesis, fluorescence microscopy, proteomics, and functional studies. We demonstrate that ZorAB shares the stoichiometry of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…It is possible that these appendages have evolved independently from the Exb/Tol-like transmembrane scaffold, and were later incorporated as proteins diverged and performed a broad range of biological functions. Future research focusing on characterising the functions of these DUF domains could help discover new biological systems and functions, such as the recently characterised Zorya anti-phage defence system (17). All GIT proteins lack a defined Plug+Linker domain and have a compact peptidoglycan-binding (PGB) domain in the B subunit.…”
Section: Generic Ion Transportersmentioning
confidence: 99%
“…It is possible that these appendages have evolved independently from the Exb/Tol-like transmembrane scaffold, and were later incorporated as proteins diverged and performed a broad range of biological functions. Future research focusing on characterising the functions of these DUF domains could help discover new biological systems and functions, such as the recently characterised Zorya anti-phage defence system (17). All GIT proteins lack a defined Plug+Linker domain and have a compact peptidoglycan-binding (PGB) domain in the B subunit.…”
Section: Generic Ion Transportersmentioning
confidence: 99%
“…The rotation of these flagella is powered by ion-powered rotary ion-pumps known as stators 13 . Recent structural characterization of the proton powered stators revealed that the stators are heteroheptamers (MotA 5 MotB 2 ), and this has now been observed in sodium powered stators (PomA5PomB2 3 ), in ion pumps (GldM5GldN2 4 , ExbB5ExbD2 5,6 ) and most recently in phage defense systems (ZorA5ZorB2 7 ). These ion-powered rotary machines (IRMs) 8 have highly diverse downstream functions, among which one is an essential gene for bacterial motility ( motAB ).…”
Section: Introductionmentioning
confidence: 99%